Imagining the impossible: magical, scientific, and religious thinking in children - Rosengren, Karl Sven; Johnson, Carl N.; Harris, Paul L. (Cambridge University Press, 2000)
This volume, first published in 2000, is about the development of human thinking that stretches beyond the ordinary boundaries of reality. Various research initiatives emerged in the decade prior to publication exploring such matters as children's thinking about imaginary beings, magic and the supernatural. The purpose of this book is to capture something of the larger spirit of these efforts. In many ways, this new work offers a counterpoint to research on the development of children's domain-specific knowledge about the ordinary nature of things that has suggested that children become increasingly scientific and rational over the course of development. In acquiring an intuitive understanding of the physical, biological or psychological domains, even young children recognize that there are constraints on what can happen. However, once such constraints are acknowledged, children are in a position to think about the violation of those very same constraints - to contemplate the impossible